Poverty Reduction in Egypt : Diagnosis and Strategy, Volume 2. Annex Tables - World Bank (Washington, DC, 2013)
The report, the first in an ongoing program, presents the results of a statistical analysis of household-level data for the periods 1995/1996, and 1999/2000, as a contribution to the preparation of a comprehensive poverty reduction strategy in Egypt. Despite considerable progress towards improving some of the non-income dimensions of poverty, more needs to be done to ease poverty. The main findings suggest a changing picture of poverty in the country, where poverty patterns changed from the urban-rural divide that had characterized the past, to a geographical/regional pattern, highlighting the lack of education as the strongest correlate of poverty. Statistics show that while inequality rose slightly for Egypt as a whole, the level was still comparable to other middle income countries; unemployment was high in urban areas; and, gender differences in poverty were small at an overall level, but were significant across regions, particularly in rural areas. Given the changing, complex picture of poverty in Egypt, a poverty reduction strategy will have to be comprehensive, yet flexible, hence, the report suggests a more sustainable growth in jobs, productivity, and incomes for the poorest; improved educational opportunities both for men, and women; reversal of growing, regional disparities in incomes, opportunities, and services; and, provision of safety nets that protect the most vulnerable.